The hydro-ethanolic extract of Scoparia dulcis Linn inhibits allergic airway inflammatory responses in murine asthma models - Jones Ofori-Amoah; Cynthia Amaning Danquah; Kwesi Boadu Mensah; Emmanuel Akomanin Asiamah; George Owusu; Jones Lamptey; Michael Frimpong Baidoo (Elsevier, 2024)
Background: Inflammatory responses, including airway inflammation, hyper-responsiveness, mucus hyper-secretion, prostaglandins and Th2 cytokines infiltration in the airway submucosa, frequently occur in allergic respiratory disorders. This study sought to investigate the effects of the hydro-ethanolic extract of Scoparia dulcis (SDE) on allergic airway inflammation, airway hyper-responsiveness, goblet cell hyperplasia, mucus hypersecretion, Th2 cytokines and prostaglandin (PG)-D2 using murine asthma models. Methods: Allergic asthma was induced in healthy guinea-pigs, and mice, by exposing them to ovalbumin (OVA) sensitization and challenge, and treatment with either 2 ml/kg normal saline, 10 mg/kg salbutamol, 10 mg/kg prednisolone, 50, 100, or 250 mg/kg of SDE per os. The percentage protection against pre-convulsive dyspnoea after methacholine challenge in OVA-induced asthmatic guinea-pigs was determined for each treatment regime, and histopathological examinations thereafter conducted on the excised lungs. Periodic acid-Schiff staining was also performed to identify goblet cell hyperplasia and mucus hypersecretion in these lung tissues. Lung tissue homogenates and serum from OVA-induced asthmatic mice were also assayed for PGD2, interleukins (IL)-5 and -13 levels using monoclonal antibody-based mouse ELISA kits. Results: SDE treatments prolonged the time taken for pre-convulsive dyspnoea to occur after methacholine challenge in OVA-induced asthmatic guinea-pigs; indicative of a positive activity against airway hyper-responsiveness. Histopathological studies also showed that SDE significantly inhibited (p ≤ 0.05) pulmonary infiltration of leukocytes, inflammatory cell accumulation, airway smooth muscle thickening and goblet cell hyperplasia. Serum and lung tissue concentrations of PGD2, IL-5 and IL-13, significantly elevated (p ≤ 0.001) following allergic asthma induction in mice, were significantly reduced (p ≤ 0.01) back to within normal levels after SDE treatments. Conclusion: The plant extract exhibited anti-asthmatic and anti-inflammatory properties, as it reduced the severity of allergic inflammation and hyper-reactivity, as well as PGD2 and Th2 cytokines infiltration in the airway; and these effects could be exploited for future management of asthma.